2018
DOI: 10.1093/glycob/cwy057
|View full text |Cite
|
Sign up to set email alerts
|

Sialylated keratan sulfate proteoglycans are Siglec-8 ligands in human airways

Abstract: Human siglecs are a family of 14 sialic acid-binding proteins, most of which are expressed on subsets of immune cells where they regulate immune responses. Siglec-8 is expressed selectively on human allergic inflammatory cells-primarily eosinophils and mast cells-where engagement causes eosinophil apoptosis and inhibits mast cell mediator release. Evidence supports a model in which human eosinophils and mast cells bind to Siglec-8 sialoglycan ligands on inflammatory target tissues to resolve allergic inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 52 publications
3
43
0
Order By: Relevance
“…MAb BKS-1(+) was raised to a keratanase-generated [N-acetylglucosamine-6-sulfate (GlcNAc-6-S)] stub neoepitope at the non-reducing terminus of corneal and skeletal KS (Akhtar et al 2008). Two pattern recognition lectin receptors, sialic acid binding Ig-like lectins (Gonzalez-Gil et al 2018), and dendritic cell Langerin identify sialylated KS and the galactose-6 sulfate epitope on KS.…”
Section: Ks Antibodiesmentioning
confidence: 99%
“…MAb BKS-1(+) was raised to a keratanase-generated [N-acetylglucosamine-6-sulfate (GlcNAc-6-S)] stub neoepitope at the non-reducing terminus of corneal and skeletal KS (Akhtar et al 2008). Two pattern recognition lectin receptors, sialic acid binding Ig-like lectins (Gonzalez-Gil et al 2018), and dendritic cell Langerin identify sialylated KS and the galactose-6 sulfate epitope on KS.…”
Section: Ks Antibodiesmentioning
confidence: 99%
“…Nonetheless, KS indeed apparently binds to Gal-7 as with the other galectins. On the glycosaminoglycan side, versatility to act as a molecular glue is further achieved by an α2,3-sialylated branch that is a counter-receptor for Gal-8N (aside from Gal-3) 22 and for human siglec-8 69 . The 6′-O-sulfation of Gal serves as a secondary motif for the binding of human siglec 70 (although this cannot be extrapolated among species), because murine siglec-F ligands do not require 6′-O-sulfation by any of the two galactose 6-O-sulfotransferases (KSGal6ST, C6ST-1) 71 .…”
Section: Discussionmentioning
confidence: 99%
“…Testing of a second saline installation from 1 patient (from donor 64 [Fig 2, B]) revealed that the initial nasal lavage efficiently removed essentially all of the Siglec-8 ligand from the airway, which is consistent with its absence from the epithelium of washed tissue sections. Because we had previously found that all Siglec-8 ligands revealed by airway tissue section overlay on both cartilage and submucosal glands were carried on KS glycan chains, 14 nasal lavage samples were resolved and blotted in duplicate and tested for the presence of Siglec-8 ligands and KS (with the latter tested by using an antibody to highly sulfated KS). The major KS proteoglycans in human lavage samples overlapped but were not congruent with Siglec-8 ligand (Fig 2, B), which is consistent with the conclusion that not all KS proteoglycans are Siglec-8 ligands.…”
Section: A Distinct Siglec-8 Ligand On the Human Airway Mucus Layer Imentioning
confidence: 99%